Influence Of Multiple Blended Binders On Engineering Properties And Durability Of Concrete - Arshad, Mohd Fadzil (2010)
The influence of multiple blended binders in the forms of binary blended cement (BBC) and ternary blended cement (TBC) on the properties and performance of concrete is investigated. The mineral admixtures used are silica fume(SF), fly ash (FA), metakaolin (MK) and rice husk ash (RHA). They are used to partly replace the cement by direct replacement method on mass-to-mass basis. The mix proportions of the concretes are kept nominally the same with constant water/binder ratio and the same superplasticizer content for all concrete mixes, so as to isolate the effect of each binder type. Most of the mineral admixtures used are abundantly available in the country and analyses performed indicate their compliance with standard specification requirements as pozzolan. They are used to replace ordinary Portland cement (OPC) at replacement level of 0 (control mix) to 40% (TBC mix). Analyses on the binders also exhibit their compliance with standard specification requirements which are comparable to OPC. The engineering properties of the TBC concretes are generally comparable with those of OPC and better than OPC:FA BBC concrete when cured continuously in water. The durability performance of the TBC concrete exposed to air is found to be comparable to that OPC concrete. Nonetheless when exposed to sulphate and chloride environments the durability performance seems to be more effected in comparison to the OPC concrete. This could be due to the very early exposure to the aggressive environments